Evidence for immunomodulation and apoptotic processes induced by cationic polystyrene nanoparticles in the hemocytes of the marine bivalve Mytilus. (October 2015) - Canesi, L.; Ciacci, C.; Bergami, E.; Monopoli, M.P.; Dawson, K.A.; Papa, S.; Canonico, B.; Corsi, I.
Abstract: Polymeric nanoparticles can reach the marine environment from different sources as weathering of plastic debris and nanowaste. Nevertheless, few data are available on their fate and impact on marine biota. Polystyrene nanoparticles (PS NPs) can be considered as a model for studying the effects of nanoplastics in marine organisms: recent data on amino-modified PS NPs (PS-NH2 ) toxicity in sea urchin embryos underlined that marine invertebrates can be biological targets of nanoplastics. Cationic PS NPs have been shown to be toxic to mammalian cells, where they can induce apoptotic processes; however, no information is available on their effects and mechanisms of action in the cells of marine organisms. In this work, the effects of 50 nm PS-NH2 were investigated in the hemocytes of the marine bivalve Mytilus galloprovincialis . Hemocytes were exposed to different concentrations (1, 5, 50 μg/ml) of PS-NH2 suspension in ASW. Clear signs of cytoxicity were evident only at the highest concentrations (50 μg/ml). On the other hand, a dose dependent decrease in phagocytic activity and increase in lysozyme activity were observed. PS-NH2 NPs also stimulated increase in extracellular ROS (reactive oxygen species) and NO (nitric oxide) production, with maximal effects at lower concentrations. Moreover, at the highest concentration tested, PS-NH2 NPs induced apoptotic process, as evaluated by Flow cytometry (Annexin V binding and mitochondrial parameters). The results demonstrate that in marine invertebrates the immune function can represent a significant target for PS-NPs. Moreover, in Mytilus hemocytes, PS-NH2 NPs can act through mechanisms similar to those observed in mammalian cells. Further research is necessary on specific mechanisms of toxicity and cellular uptake of nanoplastics in order to assess their impact on marine biota. Highlights: Nanoplastics-NPs from plastic debris in oceans may become a threat to marine biota. Cationic polystyrene NPs showed toxicity in mammalian cells and sea urchin embryos. The in vitro effects of PS-NH2 were investigated in Mytilus hemocytes. PS-NH2 affected several immune parameters and induced pre-apoptotic processes. The immune function represents a significant target for PS-NPs In marine invertebrates.